Synthesis and electrical properties of CuBr2 complexes with 1,10-phenanthroline monohydrate - KAKI, ESRA HACER (WALTER DE GRUYTER GMBH, 2008)
Using 1,10-phenanthroline monohydrate and CuBr2 in molar ratios of 1:1 and 2:1, in CH3OH/H2O (phi(r) = 1:1), the complexes [(phen)CuBr2](2), (I), and {[(phen)(2)CuBr]Br center dot H2O}, (II), have been prepared. The hydrogen bondings and aqua bridges between coordinated and noncoordinated bromides of II have been observed by XRD. Complex II has a triclinic crystal structure with distorted trigonal bipyramidal coordination geometry. Possibilities of ligand exchange with hydroxide or ammonia have been examined in both complexes. While the mononuclear complex II is stable in a refluxed ammonia solution and the complex {[phen)(2)CuBr]Br center dot 3H(2)O}, (IV), trihydrate of II, is obtained; the binuclear complex I reacts with the ammonia solution to replace one of its bromides in the subunits with hydroxide to give {[(phen)(2)Cu2Br2(OH)(2)]center dot 4H(2)O}, (III). Structural and electrical properties of the complexes have been investigated by elemental analysis, vibrational and electronic spectroscopy, mass spectrometry, TGA, XRD and the four-point probe method. The temperature coefficients of resistivity and the activation energies of the complexes have also been obtained. All complexes behave as intrinsic semiconductor in the temperature range of 310-440 K. (C) 2008 Institute of Chemistry, Slovak Academy of Sciences.
Keywords: 1,10-phenanthroline; copper(II) bromide; electrical conductivity; semiconductor; CRYSTAL-STRUCTURE; ELECTRONIC-PROPERTIES; COMPARATIVE CRYSTALLOGRAPHY; STRUCTURAL PATHWAYS; DNA; PHENANTHROLINE; PERCHLORATE; COPPER(II); TRANSITION